INCIDENCE DU MICROBISME SUR LA PRODUCTIVITE AVIAIRE DANS LA FILIERE CHAIR. - SAIDANE, ZOHRA (My University, 2018)
This study was inspired by the problems met in the poultry industry and illustrious the hygienic, technical importance knowledge towards damaging germs to improve the health of animals and consequently profitability the breeding. In the first part, this work raises a bibliographical study on the reproduction and the production of chicken, the control of the atmosphere in rearing houses and finally the main influences of the microbism on the productivity in poultry farming. The second part of this work aims at describing better the nuisances of germs looked for in the air and the surfaces to know salmonellas, enterobacteria,staphylococci and pseudomonas on the viability of the livestock of heavyweight and the outbreak of the hatching eggs in the hatchery. As matter of fact, one hundred and eighty four takings were isolated on the various levels of the chain of reproduction (center of breeding, reproduction and the hatchery), it emerges from this study that the fall production of chicks is the fact of a fall in production of accumulated of the hatching eggs, in the reduction in fertility off eggs and in embryonic mortalities further to a traffic of pathogenic germs having influence on the viability of the chicks. Face à ce constat clinique, nous nous sommes incités à réaliser des analyses bactériologiques pour mettre en évidence les germes pathogènes tels que les entérobactéries, les salmonelles, Les staphylocoques responsables d’une part de cette mortalité.
Keywords: l’industrie avicole; le microbisme; le taux de ponte et l’éclosion des OAC.; poultry industry; microbism; rate of heavyweight; hatching eggs